HEPATITIS C: THE CURRENT STATE OF THE PROBLEM (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article provides a generalized overview of modern virological, diagnostic, and therapeutic aspects of hepatitis C and discusses the latest achievements in this field. Standard therapy for chronic hepatitis C with pegylated forms of interferon-α and ribavirin leads to viral elimination in 40-50% of patients infected with HCV genotype 1 and in 80% of patients infected with HCV genotypes 2 and 3. Today, based on a better understanding of the molecular virology and pathogenesis of hepatitis C, new antiviral therapy strategies are being developed, which are likely to complement existing treatment options in the near future.